Sumber-Sumber Informasi Tentang Kesehatan Reproduksi Dengan Kesiapan Menghadapi Menarche - Endang Khoirunnisa (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: Adoslescents are a unique transitional period and is characterized by a variety of physical changes, emotional and psychological. Adolescence is the age of 10-19 years, a period which is special and important, because it is a period of maturation of the human reproductive organs, and is often called the future state pubertas. Elemantry school Wojo 2 Bangunharjo Sewon Bantul there are 60% students do not understand about reproductive health issues in particular preparedness menarche.Objective: To know the relationship of the sources of information about reproductive health preparedness for menarche in primary school Wojo 2 Bangunharjo Sewon Bantul.Method: Research of method used is a descriptive approach to correlation. The population used in this study were fifth and sixth grade students of SD Negeri Wojo 2 Bangunharjo Sewon Bantul. with a sample of 46 students. Pemelihan sample by using a data collection sheet questionnaire was conducted in May 2013.Results: Of the 46 samples obtained data based on student age 12 years 51.0%, and 49.0% 11 years, sources of reproductive health in fifth and sixth grade students of SD Negeri Wojo 2 Bangunharjo Sewon Bantul who have a good source of as many as 24 percent of respondents with 70.6%. And girls who had menarche good preparedness that 35 respondents with the percentage of 76.5%.Conclusion: There is a relationship sources of information about reproductive health preparedness at menarche grader V and VI Elementary School Wojo 2 Bangunharjo Sewon Bantul.Keywords: Sources of information, preparedness menarche